2017
DOI: 10.1007/s10730-017-9319-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Decisions for Babies with Trisomy 13 and 18

Abstract: Many babies with trisomy 13 and 18 die in the first year of life. Survivors all have severe cognitive impairment. There has been a debate among both professionals and parents about whether it is appropriate to provide life-sustaining interventions to babies with these serious conditions. On one side of the debate are those who argue that there is no point in providing invasive, painful, and expensive procedures when the only outcomes are either early death or survival with severe cognitive impairment. Others s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Two recent studies that analysed survival of children with trisomy 13 or 18 beyond 1 year [ 25 , 72 ] demonstrated that although cumulative survival was low, children who were alive at their first birthday had around an 80% chance of survival to their fifth birthday, and 86% of those who survived to age 5 were likely to live to age 10 years [ 25 ]. Despite the emerging evidence that intensive care and surgical interventions improve the survival in these children [ 85 ], the debate in the medical community in relation to the interventions to be offered to infants with these trisomies is ongoing [ 85 87 ] because of severe cognitive impairment in the survivors and considerations in relation to family and societal burden [ 87 ]. Current medical experts’ view is that medical care of children with trisomies 13 and 18 should be evidence-based [ 85 ], and more consideration should be given to personalised care of these children, providing more information to parents and taking into account their hopes and wishes [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies that analysed survival of children with trisomy 13 or 18 beyond 1 year [ 25 , 72 ] demonstrated that although cumulative survival was low, children who were alive at their first birthday had around an 80% chance of survival to their fifth birthday, and 86% of those who survived to age 5 were likely to live to age 10 years [ 25 ]. Despite the emerging evidence that intensive care and surgical interventions improve the survival in these children [ 85 ], the debate in the medical community in relation to the interventions to be offered to infants with these trisomies is ongoing [ 85 87 ] because of severe cognitive impairment in the survivors and considerations in relation to family and societal burden [ 87 ]. Current medical experts’ view is that medical care of children with trisomies 13 and 18 should be evidence-based [ 85 ], and more consideration should be given to personalised care of these children, providing more information to parents and taking into account their hopes and wishes [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classically, T13 and T18 have been described as lethal chromosomal abnormalities that are associated with poor quality of life. 27 Recently, however, retrospective reviews have demonstrated that 13% of T13 and 10% of T18 patients have lived past the age of 10 y with case reports of patients living to 30 y old. 6,15 Equally important, quality of life surveys performed by parents of T13 and T18 children universally reported their child's quality of life as high with an average of 92.7 of 100 (range, 80-100) on validated scales.…”
Section: Discussionmentioning
confidence: 99%
“…32 For families who heard in pregnancy that their child would automatically not be a candidate for resuscitation or would not be considered for medical interventions due to genetics, the experience is one of perceived rejection, diminished dignity, and devaluation of their child's life. 26,28,32,33 Medical staff sensitivity to prior experiences warrant supportive listening, learning about family's hopes, and partnership in focusing on goals of care for the baby while viewing each baby as unique. 34 There exists a vibrant social media and blogging network specific to these diagnoses with families using Facebook (89%) and blogs (59%) to connect with support (90%), gather information (81%), and share information (73%).…”
Section: Family Experiencementioning
confidence: 99%